UCP3 reciprocally controls CD4+ Th17 and Treg cell differentiation - Porter, Richard; Walsh, Patrick; Mills, Kingston; Lavelle, Edward; Munoz-Wolf, Natalia (My University, 2020)
Uncoupling proteins (UCPs) are members of the mitochondrial anion carrier superfamily that can mediate the transfer of protons into the mitochondrial matrix from the intermembrane space. We have previously reported UCP3 expression in thymocytes, mitochondria of total splenocytes and splenic lymphocytes. Here, we demonstrate that Ucp3 is expressed in peripheral naive CD4+ T cells at the mRNA level before being markedly downregulated following activation. Non-polarized, activated T cells (Th0 cells) from Ucp3-/- mice produced significantly more IL-2, had increased expression of CD25 and CD69 and were more proliferative than Ucp3+/+ Th0 cells. The altered IL-2 expression observed between T cells from Ucp3+/+ and Ucp3-/- mice may be a factor in determining differentiation into Th17 or induced regulatory (iTreg) cells. When compared to Ucp3+/+, CD4+ T cells from Ucp3-/- mice had increased FoxP3 expression under iTreg conditions. Conversely, Ucp3-/- CD4+ T cells produced a significantly lower concentration of IL-17A under Th17 cell-inducing conditions in vitro. These effects were mirrored in antigen-specific T cells from mice immunized with KLH and CT. Interestingly, the altered responses of Ucp3-/- T cells were partially reversed upon neutralisation of IL-2. Together, these data indicate that UCP3 acts to restrict the activation of naive T cells, acting as a rheostat to dampen signals following TCR and CD28 co-receptor ligation, thereby limiting early activation responses. The observation that Ucp3 ablation alters the Th17:Treg cell balance in vivo as well as in vitro suggests that UCP3 is a potential target for the treatment of Th17 cell-mediated autoimmune diseases.
PUBLISHED
Keywords: Triple-negative breast cancer (TNBC); 2-Deoxy-D-Glucose (2-DG); Seahorse; Autoimmune Diseases (Multiple Sclerosis, Rheumatoid Arthritis)